Microwave and Steam Processing: A Novel Approach to Modifying the Characteristics of Reconstituted Whole Wheat Flour and Dough - Xuhua Liu; Qiangqiang Sun; Rong Yan; Yaqing Wang; Junying Wang; Liping Yang; Ligong Zhai (Molecules)
To reduce the adverse effects of bran on whole wheat flour products. In this study, seven reconstituted whole wheat flours were prepared and used to determine the effects of microwave and steam treatment on bran. We aimed to understand the effect of modification treatment on the properties of reconstituted whole wheat flour and dough. Treatment with whole wheat flour had a significant impact on the color, solubility, and swelling. As the cooking time increased, the initial temperature (To), peak temperature (Tp), and final temperature (Tc) of pasting and enthalpy (Hp) decreased. The combination of microwave and steam modification increased water absorption and stabilization time, leading to improved fermentation performance and cooking stability of the dough. The modified whole wheat flour and dough exhibited a significant decrease in crystallinity, possibly due to the degradation of the crystalline and amorphous regions of the starch granules during heat treatment. Upon modification treatment, the spiral β-turn structure was transformed into an irregular curled and β-sheet structure, and the β-sheet ratio increased significantly (p < 0.05). The modification of bran through microwave treatment (700 W for 30 s) followed by steam treatment (10 min) enhanced the processing performance of reconstituted whole wheat flour, offering substantial potential for the development of novel products and the optimization of industrial production efficiency.